Рус-Бухоро урушларидаги ҳарбий ҳаракатлар тарихининиг манбаларда ёритилиши - Каландарова, Ф.А (ILIM hám JÁMIYET, 2023)
This article examines the military operations in the Russian-Bukhara wars and their coverage in local sources. Also, in